Application Analysis Study and Implications of Rules "Al-`Ibratu Bi `Umūmi Al-Lafdzi Lā Bi Khushūshi As-Sabab" In Tafsir Mafātih al-Ghoīb - Amin Mukrimun; M Misman (Bulletin of Islamic Research, 2023)
One of the asbābun-nuzūl rules that has caused debates among ulama is the rule "Al-`Ibrotu Bi `Umūmi Al-Lafdzi Lā Bi Khushūshi As-Sabab". The majority of Ulama are pro with these rules, while the minority of them against it. One of the great Ulama of proficient mufassir is Al-Imām Fakhruddīn Ar-Rāzī. Many of these rules he poured in his monumental creation, Tafsir Mafātih Al-Ghoīb. In this case, The researcher wants to analyze the application and implications of this rule in the interpretation of Mafātih Al-Ghoīb in five verses : Those are Surah al-Baqarah (2): 174, Surah al-Māidah (5): 33, Surah al-An`ām (6): 93, Surah al-A`rāf (7): 31, and Surah al-Anfāl  (8): 27. The purpose of this study was to determine the application and implications of the rule "Al-`Ibrotu Bi `Umūmi Al-Lafdzi Lā Bi Khushūshi As-Sabab" in the interpretation of Mafātih Al-Ghoīb in these five verses. The method in this writing is qualitative methods, that is research by using literature studies sourced from relevant literacy. With this analytical study, it will be known how the application and implications of the rule "Al-`Ibrotu Bi `Umūmi Al-Lafdzi Lā Bi Khushūshi As-Sabab" in these 5 verses. The result of this study is that Al-Imām Fakhruddīn Ar-Rāzī has carried out the procedure for applying the rules in interpreting the 5 verses correctly, The procedure is chronology and the reason for the revelation of the 5 verses is specific to a certain person and the redaction of the 5 verses uses a redaction by generality.  While the implications for the interpretation of the 5 verses are: a) Surah al-Baqarah (2): 174, has implications for the prohibition of hiding knowledge, b) Surah al-Māidah (5): 33, has implications for the prohibition of making damage on earth, c) Surah al-An`ām (6): 93, has the implication of prohibiting lying in the name of Allah, d) Surah al-A`rāf (7): 31, has implications for the obligation to wear the best clothes in worship, and e) Surah al-Anfāl  (8): 27-28, has implications for the prohibition of treason. The results of this study can be used as a method of making legal decisions not only in the past, but can also be applied to modern-contemporary, because of Qur'an is intended for all mankind throughout the ages. This is what makes the Qur'an a book that "Ṣālih Li Kulli Zamān Wa Makān" or a book whose meaning and message can apply throughout the ages.